PENGARUH KOMPOSISI MEDIA TANAM DAN DOSIS PUPUK ORGANIK CAIR NASA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERONG (Solanum melongena L.) VARIETAS YUVITA F1 - Ferdiananda , Alief; Dita Serdani, Army; Widiatmanta , Jeka (Universitas Islam Balitar, 2023)
The aim of this research is to determine the effect of the interaction between planting media composition and dosage of Nasa liquid organic fertilizer on the growth and yield of eggplant (Solanum melongena L) var. YuvitaF1. The research was carried out in Dukuh Jlimut, Plosokerep Village, Sananwetan District, Blitar City with an altitude of 150-200 in March – June 2023. The research used a 2 factorial Randomized Block Design. Factor I is the composition of the planting medium (M) which consists of 3 levels, namely M1: soil: Goat kohe fertilizer (5:1), M2: Soil: Rice husks: Goat kohe (3:2:1), M3: Soil: Cocopeat : Kohe Goat (3:2:1). Factor II is the dose of Nasa POC fertilizer (P) which consists of 4 levels, namely P1 = 0 ml/polybag (without POC fertilizer), P2: 3 ml/polybag, P3: 6 ml/polybag and P4: 9 ml/polybag . The experiment was repeated 3 times so there were 36 experimental units. The variables observed were plant height (cm), number of fruit and fruit weight at harvest (grams). The average observation results were analyzed using a variance test (α = 5%) and followed by a 5% Honestly Significant Difference Test (BNJ). The research results showed that there was a real interaction between the composition of the planting medium (M) and the Nasa POC dose (P) on the variables of plant height, number of fruit and fruit weight of eggplant plants. The best results were obtained in the M1 planting media composition treatment (soil: goat kohe with a ratio of 5:1) and a Nasa POC dose of 6 ml/polybag (M1P3) for these 3 variables.